2017
DOI: 10.1002/2017rs006304
|View full text |Cite
|
Sign up to set email alerts
|

High‐Isolation Low Cross‐Polarization Phased‐Array Antenna for MPAR Application

Abstract: The design and analysis of 12 × 12‐element planar array of a dual‐polarized aperture‐coupled microstrip patch antenna operating in the frequency band of 2.7 GHz to 3.0 GHz for multifunction applications are presented. High‐isolation between horizontal and vertical polarization ports and low cross‐polarization are achieved through an aperture‐coupled feed. The reflection coefficient and the isolation of horizontal and vertical ports at different scan angles are examined. The array antenna is fabricated and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…This is because on a finite ground-plane the surface waves are reflected and diffracted at the edges of the substrate, which results in a significant amount of energy loss [4,5]. To date numerous techniques have been explored to improve the radiation performance of patch antennas implemented on substrates [6][7][8]. This includes incorporating photonic bandgap (PBG) or electromagnetic bandgap (EBG) structures around the radiating elements [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This is because on a finite ground-plane the surface waves are reflected and diffracted at the edges of the substrate, which results in a significant amount of energy loss [4,5]. To date numerous techniques have been explored to improve the radiation performance of patch antennas implemented on substrates [6][7][8]. This includes incorporating photonic bandgap (PBG) or electromagnetic bandgap (EBG) structures around the radiating elements [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…So far, to our knowledge, similar theoretical analysis and practical implementations have not been reported. Compared to previous approaches based on mirroring elements [11][12][13][14][15][16][17][18][19], this approach is array based. To obtain an optimal XPD, the only requirement is the identity of the mirrored subarrays, regardless of the scale and their original XPD.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the near-field coupling between the densely arranged elements, the effectiveness of this method was severely reduced. Conventional study showed that mirroring the neighbouring radiating elements could improve the XPDs [11][12][13][14][15][16][17][18][19]. However, while the near-field coupling was not considered, mirroring neighbouring elements will result in significantly enlarged feeding networks.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, since the network of weather surveillance (WSR-88D) radars has been upgraded to dualpolarised radars, it is required that MPAR be capable of transmitting and receiving horizontally and vertically polarised waves simultaneously. In terms of bandwidth, MPAR is required to operate from 2.7 to 2.9 GHz, which is the frequency band assigned for aeronautical radio navigation [3,4].…”
mentioning
confidence: 99%